2021
DOI: 10.3390/molecules26185504
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide N-acetylgalactosaminyltransferase-Associated Phenotypes in Mammals

Abstract: Mucin-type O-glycosylation involves the attachment of glycans to an initial O-linked N-acetylgalactosamine (GalNAc) on serine and threonine residues on proteins. This process in mammals is initiated and regulated by a large family of 20 UDP-GalNAc: polypeptide N-acetylgalactosaminyltransferases (GalNAc-Ts) (EC 2.4.1.41). The enzymes are encoded by a large gene family (GALNTs). Two of these genes, GALNT2 and GALNT3, are known as monogenic autosomal recessive inherited disease genes with well characterized pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 134 publications
(161 reference statements)
0
18
0
Order By: Relevance
“…We identified genes associated with protein modification with increased expression in ethanol-fed non-irradiated mosquitoes relative to water-fed non-irradiated mosquitoes. One of these, polypeptide N-acetylgalactosaminyltransferase 5 belongs to a family of glycotransferases that participate in glycosylation of extracellular matrix (ECM) protein components ( Kato et al, 2021 ). The other gene, aminopeptidase N encodes a membrane-localized enzyme that removes amino acids from the N-terminal of proteins ( Turner, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We identified genes associated with protein modification with increased expression in ethanol-fed non-irradiated mosquitoes relative to water-fed non-irradiated mosquitoes. One of these, polypeptide N-acetylgalactosaminyltransferase 5 belongs to a family of glycotransferases that participate in glycosylation of extracellular matrix (ECM) protein components ( Kato et al, 2021 ). The other gene, aminopeptidase N encodes a membrane-localized enzyme that removes amino acids from the N-terminal of proteins ( Turner, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GALNTL6 gene encodes the membrane-bound protein N-acetylgalactosaminyltransferase like 6, which has a significant role in the pathway of protein glycosylation (43,44). There are no previous reports of a role of this gene in the context of diabetes and its vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…According to genome-wide association studies (GWAS), a subset of genes encoding O-glycosylation enzymes have been found to be highly associated with ASD and schizophrenia [ 51 , 105 ]. For example, GALNT9 , which is mainly expressed in the brain, was reported to be associated with ASD [ 51 , 105 , 106 ]. In clinical studies, microdeletions of chromosome 2q have also been reported in ASD individuals with developmental delay, language delay, communication disorders, and social anxiety [ 107 , 108 ].…”
Section: O-glycosylationmentioning
confidence: 99%